Pemanfaatan Museum Negeri Sumatera Utara Sebagai Sumber Belajar Sejarah Tingkat SMA - Olindo Sinaga (Education & Learning, 2021)
This study aims to determine the use of the State Museum of North Sumatra as a source of learning history at the high school level in the city of Medan. In the learning process the teacher can choose learning resources that are in accordance with the material. One of the learning resources that can be used by history teachers in the city of Medan is the North Sumatra State Museum. It is hoped that the use of museums as a learning resource can enrich historical knowledge and can foster interest and historical awareness. The research method used is library research (library research), which is research based on searching the literature related to the issues to be discussed. The data in this library research was obtained through digging and tracing the use of museums as learning resources by history teachers at SMA PAB 1 Medan, SMA Negeri 11 Medan, SMA Negeri 5 Medan, SMA Al-Ulum Medan, journals, and internet sites with reliable sources. The results show that the museum can be used as a learning resource by high school teachers in Medan and has been adjusted to the 2013 curriculum.